LITERATURE REVIEW: IMPLEMENTASI PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) DI FASILITAS KESEHATAN TINGKAT PERTAMA - Destanti, Ruri; Misnaniarti, Misnaniarti; Syakurah, Rizma Adlia (LPPM STIKES BHAKTI HUSADA BENGKULU, 2025)
ABSTRACTProlanis is one of the promotive and preventive strategies carried out by BPJS Kesehatan to reduce or prevent complications of chronic diseases suffered by participants as well as to control health service costs. The target of this program is all BPJS Kesehatan participants with chronic diseases (type 2 diabetes mellitus and hypertension) with the aim of encouraging participants with chronic diseases to achieve optimal quality of life with an indicator of 75% of registered participants who visit FKTP having